The Expressive Role of Rhythm and Meter in Schumann’s Late Lieder - Harald Krebs (Gamut: Online Journal of the Music Theory Society of the Mid-Atlantic, 2009)
Rhythm and meter are significant expressive elements in Robert Schumann’s music. Nowhere is his awareness of the expressive potential of rhythm and meter more evident than in his Lieder, where the presence of a text makes it possible to determine just what Schumann was trying to express. The author focuses on three practices: distortion of the poetic rhythm, metrical dissonance, and hypermetric irregularity. Only Schumann’s late songs are addressed, not only because they are generally less familiar, but also because two of the practices to be discussed (distortion of poetic rhythm and hypermetric irregularity) are especially common in them. This article is part of a special, serialized feature: A Music-Theoretical Matrix: Essays in Honor of Allen Forte (Part I).